Association Between Lifetime Sexual Violence and Recent Traumatic Brain Injury Among Adults: 2017 Connecticut Behavioral Risk Factor Surveillance System - Waltzman, Dana (Journal of interpersonal violence, 2024)
Sexual violence (SV) is a critical public health problem that is associated with numerous negative health consequences, including immediate- and long-term physical and mental health conditions and health-risk behaviors. Some of these health-risk behaviors (e.g., substance use, unsafe driving practices, poor mental health, lower impulse control, and abnormal brain circuitry) might increase the risk for sustaining a traumatic brain injury (TBI). A TBI causes neurological or neuropsychological changes and may also lead to various symptoms that affect a person’s cognition, mobility, behavior, and mental health. Determining if those who have experienced SV are at increased risk of sustaining a TBI in their lifetime is critical given the high prevalence and health impacts of SV, the potential vulnerability to TBI after SV, and the known detrimental effects of TBI. This exploratory study examined data from the 2017 Connecticut behavioral risk factor surveillance system and found that lifetime SV victimization (controlling for age and sex) was associated with increased odds of reporting a recent TBI in the past 12 months (adjusted odds ratio [AOR] = 2.1; 95% confidence interval [CI] [1.03, 4.21]). Further research is needed to better understand how SV history is related to the risk of sustaining a TBI. Healthcare professionals can support patients who experience SV by providing resources to help reduce associated physical and mental health conditions and health-risk behaviors.